Bailey & Scott's diagnostic microbiology. - Tille, Patricia M. (Elsevier, 2014)
The new 12th edition of Bailey & Scott's Diagnostic Microbiology solidifies its reputation as the classic text in the field of microbiology. This new edition features the same comprehensive, authoritative content - and adds new and updated material throughout. The team of authors includes three well-respected clinical microbiologists, all of whom have experience both in the classroom and the clinical laboratory